2015
DOI: 10.1111/1467-6427.12069
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of family functioning in adolescents who self‐harm

Abstract: This study compares the self-reported family functioning of 21 adolescents presenting at four UK medical wards with self-harming behaviour with those obtained from a sample of adolescents drawn from the local community. Adolescents hospitalized for self-harm reported that their families were more dysfunctional than healthy controls on the family perceptions scale. However, this difference was not observed when covariates such as emotional and behavioural distress were controlled for. Poor levels of agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Among dyads where the adolescent is experiencing mental illness, such as major depressive disorder, adolescents typically report poorer family functioning than their parents (e.g., Tamplin, Goodyer, & Herbert, ). Recently, Palmer, Welsh, and Tiffin () extending this finding to NSSI, reporting that the sampled adolescents who presented to a medical ward in England for an episode of self‐injury reported significantly poorer family functioning than their parents. Palmer et al.…”
Section: Family Functioning and Self‐injurymentioning
confidence: 91%
See 1 more Smart Citation
“…Among dyads where the adolescent is experiencing mental illness, such as major depressive disorder, adolescents typically report poorer family functioning than their parents (e.g., Tamplin, Goodyer, & Herbert, ). Recently, Palmer, Welsh, and Tiffin () extending this finding to NSSI, reporting that the sampled adolescents who presented to a medical ward in England for an episode of self‐injury reported significantly poorer family functioning than their parents. Palmer et al.…”
Section: Family Functioning and Self‐injurymentioning
confidence: 91%
“…Palmer et al. 's () findings indicate that parents may not be aware how poorly the family unit is perceived by their adolescent with a history of self‐injury. However, this study treated parent and adolescent reports as independent which is inappropriate given the intrafamilial correlations of reported family functioning.…”
Section: Family Functioning and Self‐injurymentioning
confidence: 99%
“…Family function has been defined as the interactions between-and reactions to-family members [11], and such interactions being dysfunctional has been related to mental health disturbances and higher rates of suicidal behavior during adolescence [6,9,10]. In line with this, it has been demonstrated that adolescents who self-harm perceive significant impairments in family function [12]. Several mechanisms have been proposed to explain the relationship between family dysfunction and suicidal behavior in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires have often been used in research, arm, predominantly to assess prevalence and identify reasons given for self-harm (Nock & Prinstein, 2004;Lloyd-Richardson, Perrine, Dierker and Kelley, 2007;Palmer, Welsh & Tiffin, 2016). One difficulty with the use of questionnaires to understand the reasons why people self-harm is that the very use of the measure limits the choices for the respondent.…”
Section: Introductionmentioning
confidence: 99%